Pengaruh Program Literasi Sekolah terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Aulia, Alfis Savinah; Maghfiroh, Nadzrotul; Faruq, Ach. Zainal; Masodi, Masodi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This research discusses the influence of the School Literacy Program (PLS) on elementary school students' critical thinking abilities.  The results of the literature study show a positive relationship between literacy and critical thinking, where adequate literacy is the foundation for better critical thinking skills.  The success of PLS, however, is highly dependent on several key factors: relevant and interesting program design, the quality of reading materials, the active role of teachers as facilitators and role models, and access to adequate technology.  Barriers to access and relevance of reading materials are challenges that need to be overcome. A holistic and integrated approach to PLS implementation is crucial to achieving optimal results. Further research is needed to empirically test these relationships and identify more effective strategies.